The Aspects Of Critical Thinking Toward Students' Psychomotor Skill In Learning Of Microprocessor And Microcontroller Programming Techniques - Buditjahjanto, I.G.P. Asto; Wildan Habibi , Mohammad; Sulistiyo, Edy (Universitas Ahmad Dahlan, 2024)
This study aims to determine the effect of critical thinking aspects on students' psychomotor skills. Aspects of critical thinking include interpreting, planning, predicting, analyzing, evaluating, and decision-making. This research was applied to a microprocessor and microcontroller programming technique subject at a vocational higher school in Surabaya-Indonesia. The multiple linear regression method was chosen to analyze the effect of simultaneous and partial aspects of critical thinking on students' psychomotor skills. The results showed that there was a significant influence between aspects of critical thinking simultaneously on students' psychomotor skills. While partially, only the predicting aspect has a significant influence on students' psychomotor skills. For other aspects, there is no significant effect on students' psychomotor skills.